MICROFLORA CARBONICA DE LA LOCALIDAD DE PAGANZO, PROVINCIA DE LA RIOJA - PARTE II (Ameghiniana, 2013)
In this second part of the study of the microflora from the lower member of the Lagares Formation, the systematic descriptions of the spores belonging to eight genera of the infraturma APICULATI are given: Apiculiretusispora, Cyclogranisporites, Geminospora, Granulatisporites, Verrucosisporites, Pustulatisporites, Lophotriletes and Raistrickia.Five species (out of thirteen) are new: Apiculiretusispora papillata, A. sparsa, Geminospora ? microgranulata, Granulatisporites varigranifer y Verrucosisporites minutus. Two new combinations are established as well as a new name. The latter is referred to a species of the genus Leiotriletes which had a pre-ocupied name.